One-carbon metabolites, B vitamins and associations with systemic inflammation and angiogenesis biomarkers among colorectal cancer patients: results from the ColoCare Study. Issue 10 (28th May 2020) - Kiblawi, Rama; Holowatyj, Andreana N.; Gigic, Biljana; Brezina, Stefanie; Geijsen, Anne J. M. R.; Ose, Jennifer; Lin, Tengda; Hardikar, Sheetal; Himbert, Caroline; Warby, Christy A.; Böhm, Jürgen; Bours, Martijn J. L.; et al.
Abstract: B vitamins involved in one-carbon metabolism have been implicated in the development of inflammation- and angiogenesis-related chronic diseases, such as colorectal cancer (CRC). Yet, the role of one-carbon metabolism in inflammation and angiogenesis among CRC patients remains unclear. The objective of this study was to investigate associations of components of one-carbon metabolism with inflammation and angiogenesis biomarkers among newly diagnosed CRC patients ( n 238) in the prospective ColoCare Study, Heidelberg. We cross-sectionally analysed associations between twelve B vitamins and one-carbon metabolites and ten inflammation and angiogenesis biomarkers from pre-surgery serum samples using multivariable linear regression models. We further explored associations among novel biomarkers in these pathways with Spearman partial correlation analyses. We hypothesised that pyridoxal-5'-phosphate (PLP) is inversely associated with inflammatory biomarkers. We observed that PLP was inversely associated with C-reactive protein (CRP) ( r –0·33, P linear < 0·0001), serum amyloid A (SAA) ( r –0·23, P linear = 0·003), IL-6 ( r –0·39, P linear < 0·0001), IL-8 ( r –0·20, P linear = 0·02) and TNF α ( r –0·12, P linear = 0·045). Similar findings were observed for 5-methyl-tetrahydrofolate and CRP ( r –0·14), SAA ( r –0·14) and TNF α ( r –0·15) among CRC patients. Folate catabolite acetyl-para-aminobenzoylglutamic acid (pABG) was positively correlated with IL-6 ( r 0·27, P linear < 0·0001), and pABG was positively correlated with IL-8 ( r 0·21, P linear < 0·0001), indicating higher folate utilisation during inflammation. Our data support the hypothesis of inverse associations between PLP and inflammatory biomarkers among CRC patients. A better understanding of the role and inter-relation of PLP and other one-carbon metabolites with inflammatory processes among colorectal carcinogenesis and prognosis could identify targets for future dietary guidance for CRC patients.